Lembaga Keuangan Syariah sebagai Penggerak Investasi Emas Berkelanjutan: Perspektif Ekonomi Syariah - Chika Vinolia; Riska Alvarido; Titin Hartini (Penerbit Jurnal Indonesia, 2026)
Islamic Financial Institutions (LKS) as drivers of sustainable gold investment from the perspective of Islamic economics. Sharia-compliant gold investment serves as an alternative financial instrument that is stable, asset-backed, and aligned with Islamic principles, thereby holding strong potential to support economic sustainability within society. This research employs a descriptive qualitative approach. The qualitative method is chosen because it allows for a holistic exploration of phenomena through in-depth interpretation of practices, mechanisms, and policies implemented by Islamic financial institutions in providing gold investment products. The findings indicate that LKS play an important role in enhancing financial inclusion, offering hedging instruments against inflation, and strengthening economic stability through products such as sharia gold savings, sharia gold pawning, and gold financing. The implementation of Islamic economic principles is reflected in the use of sharia-compliant contracts, price transparency, prohibition of speculation, and ensuring lawful ownership of assets. However, the development of sustainable gold investment still faces challenges such as low public financial literacy, global gold price fluctuations, limited digital infrastructure, and public perceptions regarding the complexity of sharia products. This study emphasizes that optimizing the role of LKS through innovation, education, and regulatory strengthening is crucial to promoting gold investment that is more inclusive, secure, and sustainable in accordance with Islamic economic values.